Fibre-based saturable absorber for generation of short-pulsed fibre lasers / Mohd Fauzi Ab Rahman - Mohd Fauzi , Ab Rahman (2019)
Short-pulsed fibre lasers have received growing attention in the recent years owing to their usefulness in various scientific and industrial applications. In the early years, various saturable absorbers (SAs), mostly thin film SAs have been widely demonstrated. While these film SAs provide low cost fabrication and simple preparation, they have low thermal damage threshold, which limits their ability as portable and robust laser source designs. In comparison, fibre SAs, are much robust, stable and have relatively good thermal handling. In this research work, a compact and stable passively all fibre Q-switched or mode-locked Ytterbium-doped fibre laser (YDFL), Erbium-doped fibre laser (EDFL) as well as Thulium-doped fibre laser (TDFL) were demonstrated by incorporating several short segments of fibre SAs in a forwarded pump ring cavity configuration. These fibre SAs, possess an absorption profile which partly overlaps with the gain medium emission profile, suggesting a possible realization of optical pulses generation. Particularly, in the 1 μm region, several fibre SAs including an 8 cm long Hafnium bismuth erbium co-doped fibre (HBEDF), a 12 cm long Ytterbium-doped fibre (YDF), an 11 cm long Titanium dioxide-doped fibre (TiO2DF), and an 11 cm long Thulium-doped fibre (TDF) were verified, viable of generating Q-switched YDFL. Meanwhile, in the 1.55 μm vicinity, an 11 cm long TDF and an 11 cm long Erbium-doped fibre (EDF) were tested, possible of promoting stable Q-switched EDFL; where a 20 cm long TiO2DF was examined feasible of demonstrating both, Q-switched and mode-locked EDFL. Additionally, in the 2 μm region, an 8 cm long Holmium-doped fibre (HDF) was tested, viable of promoting stable Q-switched and mode-locked TDFL. Experimentally, the fibre SAs (TiO2DF and HDF) were verified, possessing comparable laser performances with the thin film SAs; Titanium dioxide film (TiO2F) and Holmium oxide PVA film (HOPF). Such short-pulsed fibre lasers realized by these fibre SAs would have perspective in real applications that require simplicity, mobility and excellent thermal handling for high laser power operations.